2016
DOI: 10.1208/s12249-016-0640-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nanoemulsion and Aqueous Micelle Systems of Paliperidone for Intranasal Delivery

Abstract: The objective of the study was to develop and compare the efficiency of nanoemulsion and aqueous micelle system of Paliperidone on intranasal administration. Both the formulations were evaluated for physical parameters such as globule size, pH, viscosity, conductivity and in vitro drug release studies. The reduction in spontaneous motor activity of L-dopa and Carbidopa-treated Swiss Albino mice on intranasal administration of nanoemulsion and micellar system of Paliperidone was compared with plain drug suspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The electrical conductivity measurements are facilitated for assessment of microemulsion type [14,23]. Mehta and Kaur [25] reported that very low specific conductivity (0.001-0.1 μS/cm) has presumed as water in oil (w/o) microemulsion, considering to conductivity of pure water (1.1-1.3 μS/cm) [26]. Based on this background, electrical conductivity data confirmed the generation of o/w types of microemulsions in the study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The electrical conductivity measurements are facilitated for assessment of microemulsion type [14,23]. Mehta and Kaur [25] reported that very low specific conductivity (0.001-0.1 μS/cm) has presumed as water in oil (w/o) microemulsion, considering to conductivity of pure water (1.1-1.3 μS/cm) [26]. Based on this background, electrical conductivity data confirmed the generation of o/w types of microemulsions in the study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Pidaparthi et al [ 29 ] also formulated paliperidone into an O/W nanometric emulsion for intranasal delivery. The nanoemulsion’s composition included Labrafil ® M 1944 CS (oleoyl polyoxyl-6 glyceride), Tween ® 80 (polysorbate 80-polyoxyethylene 20 sorbitan monooleate), Transcutol ® HP (diethylene glycol monoethyl ether), benzalkonium chloride and phosphate buffer (pH 6.4) (specific amounts in Table 6 ).…”
Section: Nanometric Emulsions Containing Antipsychotic Drugsmentioning
confidence: 99%
“…Paliperidone O/W intranasal nanometric emulsions were carried out in 2 studies. Despite having similar viscosities, the microemulsions developed by Patel et al [ 28 ] reached a higher drug strength, lower droplet size, good PDI, and were prepared by spontaneous emulsification, whereas the nanoemulsion developed by Pidaparthi et al [ 29 ] required more complex preparation methods and did not even report PDI values. Nevertheless, all formulations reportedly had therapeutic-like effects in pharmacodynamic studies (same animal model), despite the administered dose being 10 times less in the Pidaparthi et al case.…”
Section: Authors’ Opinionmentioning
confidence: 99%
“…Moreover, nanocrystals of aripiprazole incorporated into buccoadhesive chitosan films could also provide a rapid drug delivery to the systemic circulation [ 7 ]. Intranasal administration of PPD nanoemulsion and Tween 80—based micelles was reported to reduce the locomotor activity of mice more rapidly than that after administration of PPD suspension [ 8 ].…”
Section: Introductionmentioning
confidence: 99%